Decision making in orthopaedic trauma - Marmor, Meir (Thieme, 2017)
Few if any medical fields share the complexity of injuries and the number of available treatments that exist in orthopaedic trauma. Deciding on the most efficacious treatment can often be difficult. In this digital age with a tsunami of medical information and conflicting data on numerous approaches, practitioners who treat orthopaedic trauma often find it problematic to make ""evidence-based"" choices. Decision Making in Orthopaedic Trauma is the largest compendium of orthopaedic trauma algorithms assembled to date. The decision trees cover a broad spectrum of cases - from simple isolated fra.